Initial Trauma Database in a University Hospital in Malaysia - Affirul Chairil Ariffin; Mohamed Hajhamad; Firdaus Hayati; Nornazirah Azizan; Zamri Zuhdi; Azlanudin Azman; Ikhwan Sani Mohamad; Hairol Othman; Razman Jarmin; Jae Gil Lee (Faculty of Medicine and Health Sciences, 2024)
Indexed by MYCITE